THE ROLE OF AI IN MANAGING PERFORMING ARTS INSTITUTIONS - Pathak, Abhishek; Bhilare, Dr. Meghana; Kalra, Hitesh; Gupta, Mridula; S.Jancy; Rathore, Ashwika (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Artificial intelligence (AI) within the performance arts facilities is transforming how the arts management, administration, and community participation has always been. Performing arts troupes would previously count on human intuition and collaboration to get things occurring but currently, they are applying data-driven approaches increasingly to get things feasible and artistic things improved. This study examines the numerous aspects that AI can be used to enhance the management of performing arts organisations, with specific focus on how AI can be used to manage such activities as finances, involvement of people and the creation of new performances. It will also investigate how the use of AI tools like machine learning, predictive analytics, and natural language processing are enhancing the capacity of people to make better decisions, simplify resource use, and provide each audience with a personalized experience. The article focuses on the effective uses of AI in the world in the field of theatre, music and dance teachings through the global case studies. It also discusses similar issues such as lack of money, poor infrastructure, and employees that don't want to adjust with the times. The study also reveals how AI can alter the organization of institutions, transform the work of employees and enhance the management of talents through digital teamwork and performance data. Even though there is clear success, the study says that social, cultural and policy issues are still very important when it comes to AI in the arts.